2023
DOI: 10.3390/plants12071571
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oil of Lavandula officinalis: Chemical Composition and Antibacterial Activities

Abstract: The purpose of this study was to determine the chemical composition of the essential oil of Lavandula officinalis from Morocco using the GC-MS technique and assess the antibacterial effects against seven pathogenic bacteria strains isolated from the food origins of Salmonella infantis, Salmonella kentucky, Salmonella newport, three serotypes of Escherichia coli (O114H8K11, O127K88ac, O127H40K11) and Klebsiella. Tests of sensitivity were carried out on a solid surface using the Disc Diffusion Method. Results sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…The thyme essential oil was used as an antiparasitic or to treat minor wounds from ancient times due to its strong antimicrobial properties [21,22]. Lavender [23,24], grapefruit [25,26], bergamot [27,28], cinnamon [29,30], and rosemary [31,32] essential oils have strong antimicrobial activity and therefore are good candidates for innovative antibacterial and antifungal therapies and materials. Nevertheless, the essential oils must be loaded or encapsulated in a matrix, be it organic or inorganic, to ensure a longer release profile, and a sustained antimicrobial activity [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…The thyme essential oil was used as an antiparasitic or to treat minor wounds from ancient times due to its strong antimicrobial properties [21,22]. Lavender [23,24], grapefruit [25,26], bergamot [27,28], cinnamon [29,30], and rosemary [31,32] essential oils have strong antimicrobial activity and therefore are good candidates for innovative antibacterial and antifungal therapies and materials. Nevertheless, the essential oils must be loaded or encapsulated in a matrix, be it organic or inorganic, to ensure a longer release profile, and a sustained antimicrobial activity [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…Their (ΔG) were estimated to be −6.7 Kcal/mol, −6.6 Kcal/mol, and −6.5 Kcal/mol, respectively ( Table 1 ). Another study indicated that eucalyptol binds efficiently with the active site of the E. coli protein, and it showed a higher activity than gentamicin, with a binding energy of −5.72 kcal/mol and −5.55 kcal/mol [ 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 shows that, in general, carnosic acid and related abietane-type dipertenes extracted from rosemary showed good results/compliance with Lipinski's Rule of Five ( Lipinski et al, 1997 ) (Molecular Weight < 500 Da, # of hydrogen bond donors: Donor HB < 5, # of hydrogen bond acceptors: Acceptor HB < 10, and predicted octanol–water partition coefficient: QPlogPo/w < 5), without any observed violations ( Diass et al, 2023 , Boumezzourh et al, 2023 , Dash et al, 2015 , Khan et al, 2009 , Fajriyah et al, 2023 , Faris et al, 2023 , Zhang and Wilkinson, 2007 , Merzouki et al, 2023 ). Similarly, Table 2 shows that, in general, all compounds exhibit ADME/T properties/pharmacokinetic descriptor values falling within the range of recommended values (values in parentheses at the bottom of the Table 2 ), with no observable violations in terms of drug characteristics.…”
Section: Resultsmentioning
confidence: 99%